TINJAUAN KINERJA PETUGAS REKAM MEDIS DI RUMAH SAKIT SALAK BOGOR GUNA PENINGKATAN PELAYANAN KESEHATAN - Anggraini Agustin; Dina Sonia (Journal of Innovation Research and Knowledge, 2021)
Medical record is one of the written evidence about the service process which contains clinical data of patients during the process of diagnosis and treatment. Management of medical records in hospitals to support the achievement of orderly administration to achieve hospital goals, namely improving the quality of health services in hospitals. The purpose of this study was to determine the performance of Medical Record Officers at Salak Hospital, Bogor. This study uses a descriptive method with a quantitative approach that aims to describe the performance review of medical record officers in accordance with the facts in the field. The results of the research on the performance of the medical record officer based on the quality of work illustrate that the medical record officer has a fairly good performance, based on the quantity of work indicated that the medical record officer has a good performance, based on the supervision of the medical record officer shows that the medical record officer has a good performance, based on the presence of the medical record officer shows that the medical record officer has a good performance, and based on the conservation of the medical record officer shows that the medical record officer has a good performance.